A robust prognostic gene expression signature for early stage lung adenocarcinoma. Issue 1 (December 2016) - Krzystanek, Marcin; Moldvay, Judit; Szüts, David; Szallasi, Zoltan; Eklund, Aron
Abstract Background Stage I lung adenocarcinoma is usually not treated with adjuvant chemotherapy; however, around half of these patients do not survive 5 years. Therefore, a reliable prognostic biomarker for early stage patients would be critical to identify those most likely to benefit from early additional treatments. Several studies have searched for gene expression prognostic biomarkers for lung adenocarcinoma, but these have not yielded a widely accepted prognosticator. Results We analyzed gene expression from seven published lung adenocarcinoma cohorts for which we included only stage I and II patients who were not given adjuvant therapy. Seven genes consistently obtained statistical significance in Cox regression for overall survival. The combined signature has a weighted mean hazard ratio of 3.2 in all cohorts and 3.0 (C.I. 1.3–7.4, p < 0.01) in an independent validation cohort and is strongly correlated with previously published signatures of chromosomal instability and cell cycle progression. Conclusions The new prognostic signature, if validated prospectively, may enable better stratification and treatment of early stage lung cancer patients.